The Growth Performance of Three Selected Indigenous Tree Species at Boye Nursery Site, Southwestern Ethiopia - Semaigzer Ayalew; Dereje Egeta; Abeje Eshete; Urge Cheru; Tensay Teshome; Giche Yadesa (International Journal of Forestry Research)
The vitality of seedlings is significantly impacted by nursery activities. Among other things, the size of containers and growing media are the most important variables in producing healthy and high-quality seedlings. For that reason, this experiment took place at the Boye Nursery Site in the Jimma Zone of Ethiopia, aimed to evaluate the impact of varying growing media and pot sizes on the growth of seedlings of three significant indigenous tree species: Prunus africana, Croton macrostachyus, and Millettia ferruginea. For this purpose, three distinct soil mixtures comprising local soil, forest soil, and sand, with ratio of 3:3:1, 3:2:1, and 3:1:1, were combined with three different pot sizes (8, 10, and 12 cm). Based on a 3 × 3 factorial design with four replications, a complete randomized block design was employed. Measurements of seedling height and root collar diameter were made. According to the findings, seedlings grown in large pots exhibited significantly greater height (mean heights of 26.17, 25.19, and 22.67 cm for Millettia ferruginea, Croton macrostachyus, and Prunus africana, respectively) and larger root collar diameters (mean diameters of 0.384, 0.39, and 0.32 cm for the same species) compared to those grown in smaller pots. On the other hand, the soil mix had no effect. Therefore, to ensure better success in tree establishment, we advise using large pots for the production of Millettia ferruginea, Croton macrostachyus, and Prunus africana seedlings in these places.